2012
DOI: 10.1371/journal.pone.0035524
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analysis of Variant Haplotypes in the 5′-Flanking Region of Protein Phosphatase 2A-Bδ Gene

Abstract: Serine-threonine protein phosphatase 2A (PP2A) is a trimeric holoenzyme that plays an integral role in the regulation of cell growth, differentiation, and apoptosis. The substrate specificity and (sub)cellular localization of the PP2A holoenzymes are highly regulated by interaction with a family of regulatory B subunits (PP2A-Bs). The regulatory subunit PP2A-B/PR55δ (PP2A-Bδ) is involving in the dephosphorylation of PP2A substrates and is crucial for controlling entry into and exit from mitosis. The molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Of note, Hui-Feng Chen et al 21 estimated overall that Protein phosphatase 2A (PP2A) accounts for up to 1% of cellular protein, and that certain functional variants in haplotypes and nuclear factor 1 may regulate the transcription of the regulatory subunit gene PPP2R2D (protein phosphatase 2, regulatory subunit B, delta).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, Hui-Feng Chen et al 21 estimated overall that Protein phosphatase 2A (PP2A) accounts for up to 1% of cellular protein, and that certain functional variants in haplotypes and nuclear factor 1 may regulate the transcription of the regulatory subunit gene PPP2R2D (protein phosphatase 2, regulatory subunit B, delta).…”
Section: Resultsmentioning
confidence: 99%
“…After incubation with transient transfection treatment for 24 h, the cells were harvested and assayed for firefly and Renilla luciferase activities with a Dual-Luciferase Reporter Assay System (Promega), as in our previous study [16]. All transfections were performed in triplicate and repeated at least thrice in independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The study subjects consisted of 251 HCC case patients and 252 cancer-free controls recruited from The First Affiliated Hospital, Sun Yat-sen University, between January 2008 and October 2011. All subjects in the study were unrelated ethnic Han Chinese confirmed by ID cards and “Household Register books”, which serve as identification in China as described in our previous study [16]. The individuals were living in Guangzhou and its surrounding regions (Guangdong Province, China) in southern China, where HCC is prevalent and HBV infection has been shown to be the main attributable risk factor [17], [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PTPRE (encoded a member of the protein tyrosine phosphatase family) [Kabir et al, 2013], GLRX3 (member of the glutaredoxin oxidoreductase family) [Ohayon et al, 2010], and PPP2R2D (delta Serine-threonine protein phosphatase 2A) [Chen et al, 2012] had been reported in somatic cancer pathologies. MTG1codes for a conserved protein required for mitochondrial translation but remains still poorly understood [Barrientos et al, 2003].…”
Section: Discussionmentioning
confidence: 99%